AVALIAÇÃO E PROMOÇÃO DO CONHECIMENTO INTERDISCIPLINAR EM EQUIPES DE ESTRATÉGIA DE SAÚDE DA FAMÍLIA (ESF) DA CIDADE-SEDE DA 5ª REGIONAL DE SAÚDE DO PARANÁ - Chiconatto, Patrícia (2015)
The interdisciplinarity is not conceptualized only of exchange of knowledge, but also practical. In this context, the main objective was to diagnose and promote knowledge interdisciplinary work of Family Health Strategy (FHS) in the city Headquartes 5thRegional Health of State of Parana, Brazil. For this, a bibliometric research in the National Register of Health Facilities was held, from which they were obtained information on the number of units with teams of FHS in the city, how many and what professionals working categories. Resulting in a population of 435 professionals working in 33 health facilities. It was applied a validated and adapted questionnaire to diagnose the interdisciplinary units. Then it was carried out, using the methodology of the conversation wheel and help oh a flipchart, an interdisciplinary educational action, which aimed to raise awareness of conceptual information about interdisciplinary work. To check the results of this educational activity, a validated questionnaire was applied. The chi-square and Fisher`s exact tests were used, as well as logistic regression to assess the association between variables and the understanding of the existence of interdisciplinary work in teams. In total 214 employees participated in the survey. The perception of the existence of interdisciplinarity was statistically significant for professionals with higher education, professional practice time in the smaller institution than 5 years for those who reported the presence of collective work/team, existence of multidisciplinary meetings and planning of actions in health, and for those who mentioned that work on the FHSprovides new learning. It was also detected an association between the presence of interdisciplinary work and the factors: education, existence of collective work/team and work in the FHSprovides new learning. In general, the assessment of educational activity was positive for the promotion of interdisciplinarity in the FHS`s teams. In conclusion, it is essential to offer more educational actions with regard to interdisciplinarity, interrelating the team and the local community. Suggest a direct intervention evaluative users, or extended to the evaluation of the work to other municipalities entered the 5thRegional Health.